2017
DOI: 10.1080/15592294.2016.1249089
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of PKF118-310 as a KDM4A inhibitor

Abstract: Epigenetic modifications are functionally involved in gene expression regulation. In particular, histone posttranslational modifications play a crucial role in functional chromatin organization. Several drugs able to inhibit or stimulate some families of proteins involved in epigenetic histone regulation have been found, a number of which are FDA-approved for the treatment of cutaneous T-cell lymphoma or are in phase I/II/III clinical trials for solid tumors. Although some protein families, such as histone dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 44 publications
1
37
0
Order By: Relevance
“…On the one hand, pathological tissues and cells exhibit epigenetic imprints of the developmental or differentiation stages from which they originate and, on the other hand, they acquire disease-specific epigenetic alterations. Exciting outcomes of these comparisons are the identification of disease-specific regulators and distant enhancers regulating oncogenes, the functional characterization of mutated/aberrantly expressed chromatin and transcriptional regulators, and how these might be profitably targeted by novel (Franci, Sarno et al 2016) as well as existing therapies (Angela, Carafa et al 2016, Chun, Lim et al 2016, Martens 2016). …”
Section: Epigenome Analysis Identifies Pathways Involved In Cell Fatementioning
confidence: 99%
“…On the one hand, pathological tissues and cells exhibit epigenetic imprints of the developmental or differentiation stages from which they originate and, on the other hand, they acquire disease-specific epigenetic alterations. Exciting outcomes of these comparisons are the identification of disease-specific regulators and distant enhancers regulating oncogenes, the functional characterization of mutated/aberrantly expressed chromatin and transcriptional regulators, and how these might be profitably targeted by novel (Franci, Sarno et al 2016) as well as existing therapies (Angela, Carafa et al 2016, Chun, Lim et al 2016, Martens 2016). …”
Section: Epigenome Analysis Identifies Pathways Involved In Cell Fatementioning
confidence: 99%
“…In addition to its antimicrobial potential, it has been shown that toxoflavin acts as a small molecule inhibitor of signaling pathways and targets involved in cancer development and treatment (24,(40)(41)(42). It was also suggested as a potential promising chemotherapeutic drug candidate for different cancers (22,24,43,44).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its antimicrobial potential, it has been shown that toxoflavin acts as a small molecule inhibitor of signaling pathways and targets involved in cancer development and treatment (24,(40)(41)(42). It was also suggested as a potential promising chemotherapeutic drug candidate for different cancers (22,24,43,44). Although the clinical development of toxoflavin might be limited by its potential toxicity (19), a number of toxoflavin analogues have been prepared due to their effective biological activity and extensive use (21,45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 KDM4A relies on its demethylase activity to promote the removal of the repressive H3K9me3 mark and that of H3K36me3, a mark linked to transcriptional elongation. 12 Aberrant expression of KDM4A was observed in a variety of cancer types. 12 Aberrant expression of KDM4A was observed in a variety of cancer types.…”
mentioning
confidence: 99%